Challenges Facing Public Resources Management of Devolved Governments in Kenya: A Case of Machakos County - Nduta, Ribebe Winnifred; Shisia, Adam; Kamau, Geoffrey; Asienga, Irene (International Journal of Economics, Commerce and Management, 2017)
Public resources management has experienced many difficulties and hurdles during the short period of devolution. Of great concern is the emotive debate on the utilization of the resources given. The main objective of the study was to assess the challenges of public resources management in Machakos County. A descriptive design method was used for the study. The target population of the study included the senior, middle and lower level managers at the County Government of Machakos. The main instruments for data collection were questionnaires with both structured and open ended questions. SPSS was used to analyze the data collected. On the basis of empirical findings, the study established that there is a relationship between strategic, institutional, integrated and analytical challenges and public resources management in Machakos County. These findings therefore, yielded into recommendations for strategic, institutional, integrated and analytical improvement of public resources management in Machakos County.
Keywords: Resource Management; Devolution Challenges; County Governments; Kenya